Should I Write or Should I Not? The Investigation of the Short- and Medium-term Effects of an Expressive Writing Intervention in Reducing Depressive Symptoms, Rumination, and Intolerance of Uncertainty in College Students. A Pilot Study - Roland-Henriu GERGELY; Éva KÁLLAY (Studia Universitatis Babeş-Bolyai. Psychologia-Paedagogia)
Given the rising mental health concerns in the student population, especially regarding depression and emotion regulation difficulties, cost-effective and accessible interventions are urgently needed. Thus, the current study investigated the short- and long-term effects of an expressive writing (EW) intervention on subclinical depressive symptoms, rumination, and intolerance of uncertainty on a sample of female Transylvanian Hungarian university students. Participants engaged in a standard EW protocol, writing about distressing experiences for 15–30 minutes over four consecutive days. Outcomes were measured at baseline (T0), immediately post-intervention (T1), and at a six-week follow-up (T2). Results revealed a significant reduction in depressive symptoms from T0 to T1 and T2, with large and moderate-to-large effect sizes, respectively. While prospective anxiety (IUS-PA) decreased immediately post-intervention, it returned to baseline levels at follow-up. Inhibitory anxiety (IUS-IA) initially increased but decreased significantly by T2. Rumination showed a delayed yet significant reduction from T0 to T2. Cognitive strategies such as self-blame and acceptance improved post-intervention, while behavioral strategies showed mixed results: withdrawal decreased over time, whereas ignoring decreased initially but rebounded by T2. These findings suggest EW may be an effective short-term intervention for reducing depressive symptoms and enhancing emotion regulation. However, some benefits diminished over time, highlighting the potential need for reinforcement or complementary interventions.